The regulatory role of INSIG1 in testicular Sertoli cells in boars - Shaoxuan Zhang; Hang Zhou; Simin Liu; Jing Li; Dali Wang; Boxing Sun; Hao Sun; Shuang Liang (Theriogenology, 2026)

Effects of organic matter content on the resistivity and pore structure of waste soil - Boxing Yang; Qiang Sun; Xinchao Zheng; Yabin Liu; Jingjing Nan; Jishi Geng (Journal of Applied Geophysics, 2026)

Effects of industrial solid wastes on the rheological behavior and electrical resistivity-acoustic emission responses of cement-based grouted bodies under loading - Xinchao Zheng; Qiang Sun; Fang Liu; Yuhang Li; Boxing Yang; Ran Tang (Journal of Environmental Management, 2026)

Study on the Change Rule and Change Mechanism of the Resistivity and Thermal Conductivity of Food Waste Oil-Contaminated Soil under Different Water Content - Boxing Yang; Qiang Sun; Xinchao Zheng; Yabin Liu; Jingjing Nan (Water, Air, & Soil Pollution, 2026)

Male mites are the promising targets for control of Dermanyssus gallinae (Acari: Dermanyssidae) based on the reproductive biology research - Boxing Liu; Jiaqi He; Qi Liu; Bohan Wang; Mingjun Xiong; Weiwei Sun; Baoliang Pan (Veterinary Parasitology, 2025)

An efficient in vivo feeding method for poultry red mites, Dermanyssus gallinae (Acari: Dermanyssidae) - Boxing Liu; Qi Liu; Bohan Wang; Penglong Wang; Kexin Zhu; Jiali Meng; Huan Li; Weiwei Sun; Baoliang Pan (Veterinary Parasitology, 2025)

Effect of temperature on the radon release characteristics of red clay - Chao Gu; Qiang Sun; Lei Zhang; Liwei Zhang; Duoxing Yang; Boxing Yang; Zhenlong Ge (Journal of Environmental Radioactivity, 2024)

Lysine-specific demethylase 1 (LSD1) participate in porcine early embryonic development by regulating cell autophagy and apoptosis through the mTOR signaling pathway - Jiajia Qi; Shaoxuan Zhang; Hexuan Qu; Yanqiu Wang; Yanwei Dong; Huakai Wei; Yu Wang; Boxing Sun; Hao Jiang; Jiabao Zhang; Shuang Liang (Theriogenology, 2024)

Identification and transcriptional response of ATP-binding cassette transporters to beta-cypermethrin in the poultry red mite, Dermanyssus gallinae - Penglong Wang; Qi Liu; Tiancong Sun; Xu Wang; Bohan Wang; Boxing Liu; Huan Li; Chuanwen Wang; Weiwei Sun; Baoliang Pan (Pesticide Biochemistry and Physiology, 2024)

Activation of CncC pathway by ROS burst regulates ABC transporter responsible for beta-cypermethrin resistance in Dermanyssus gallinae (Acari:Dermanyssidae) - Penglong Wang; Huan Li; Jiali Meng; Qi Liu; Xu Wang; Bohan Wang; Boxing Liu; Chuanwen Wang; Weiwei Sun; Baoliang Pan (Veterinary Parasitology, 2024)

Function of glycogen synthase kinase3 in embryogenesis of Dermanyssus gallinae - Jiali Meng; Bohan Wang; Xiaoxiao Qi; Penglong Wang; Boxing Liu; Qi Liu; Weiwei Sun; Baoliang Pan (Veterinary Parasitology, 2023)

Effects of PM2.5 and its constituents on hemoglobin during the third trimester in pregnant women - Guilan Xie; Jie Yue; Wenfang Yang; Liren Yang; Mengmeng Xu; Landi Sun; Boxing Zhang; Leqian Guo; Mei Chun Chung (Environmental Science and Pollution Research, 2022)
Anemia has been a public health issue evoking global concern, and the low hemoglobin (Hb) concentration links to adverse pregnancy outcomes. However, the associations of PM 2.5 and its constituents with Hb and anemia in pregnant women remain unclear. In this retrospective birth cohort study, 7932 pregnant women who delivered in the First Affiliated Hospital of Xi’an Jiaotong University from 2015 to 2018 were included. The Hb during the third trimester in pregnant women was assessed before delivery. PM 2.5 and its constituents (BC, NH 4 + , NO 3 − , OM, SO 4 2− , and Dust) during pregnancy were retrieved from the V4.CH.03 product constructed by the Atmospheric Composition Analysis Group. Generalized linear regression model was applied to investigate the effects of PM 2.5 and its constituents on Hb and anemia during the third trimester in pregnant women. The means and standard deviations of PM 2.5 , BC, NH 4 + , NO 3 − , OM, SO 4 2− , and Dust were 69.56 (15.24), 10.02 (2.72), 8.11 (1.77), 14.96 (5.42), 15.36 (4.11), 10.08 (1.20), and 10.98 (1.85) μg/m 3 , respectively. Per IQR increase (μg/m 3 ) of PM 2.5 , BC, NO 3 − , and OM linked to − 0.75 (− 1.50, − 0.01), − 0.85 (− 1.65, − 0.04), − 0.79 (− 1.56, − 0.03), and − 0.73 (− 1.44, − 0.03) g/L decrease of Hb during the third trimester in multiparous pregnant women, but not for NH 4 + , SO 4 2− , Dust, and primiparous pregnant women. PM 2.5 and its constituents had no significant association with anemia, except for Dust (OR: 0.90, 95% CI: 0.82, 0.99, per IQR increase) in primiparous pregnant women. Besides, SO4 2− was of lag effects on Hb and anemia in multiparous pregnant women. Moreover, non-linear associations were found among PM 2.5 and its constituents, Hb, and anemia. Therefore, exposure to PM 2.5 and some constituents of PM 2.5 was associated with reduced Hb level during the third trimester in multiparous pregnant women. Related departments and pregnant women should take targeted actions to eliminate the detrimental effects of PM 2.5 and its constituents on pregnancy outcomes.

RNA binding protein QKI contributes to WT1 mRNA and suppresses apoptosis in ST cells - Xin Liu; Jia Guo; Mengjiao Zhou; Yuwei Yang; Mengdi Liang; Chunyan Bai; Zhihui Zhao; Boxing Sun (Genes & Genomics, 2017)